New Insights on Quality, Safety, Nutritional, and Nutraceutical Properties of Honeydew Honeys from Italy - Andrea Mara; Federica Mainente; Vasiliki Soursou; Yolanda Picó; Iratxe Perales; Asma Ghorab; Gavino Sanna; Isabel Borrás-Linares; Gianni Zoccatelli; Marco Ciulu (Molecules)
Honeydew honey is less studied than nectar honey, although it is characterized by peculiar nutritional properties. This is mainly due to its challenging production, which leads to easy counterfeiting and difficult valorization. This contribution aims to provide a comprehensive characterization of the physico-chemical, palynological, functional, and food safety properties of a large sampling of honeydew honeys collected throughout Italy. The honeydew elements, conductivity, color, antioxidant properties, total polyphenol content, hydroxymethylfurfural, major and trace elements, toxic and rare earth elements, and pesticide residues were measured in 59 samples of honeydew honey from forest, eucalyptus, fir, oak, and citrus sources. Physico-chemical and antioxidant properties were unable to differentiate the botanical origin of Italian honeydew honeys. Similarly, the mineral composition did not vary significantly, whereas rare earth elements appeared to be promising markers for classifying their origin. Multivariate analysis allowed discriminating fir honeydews from the other varieties. Concerning safety aspects, pesticide residues were detected in 90% of the samples, with fir honeydews exhibiting the lowest contamination levels, probably due to its production in less industrialized areas. Acetamiprid and imidacloprid were the most prevalent pesticide residues, but their concentrations were below the limit indicated by the EFSA. These findings suggest the need for a continuous monitoring program for contaminants to ensure safety and to assess risk.